Особливості клінічного статусу хворих із соматотропною недостатністю перед і на тлі терапії препаратами гормону росту - Большова, О. В.; Самсон, О. Я.; Вишневська, О. А.; Музь, В. А.; Зубкова, С. Т.; Кульчицька, Н. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
Patients with growth hormone deficiency that long time were without replacement therapy along with growth deficiency had changes of lipidogramma (dyslipidemiya), cardio-vascular system (decrease of blood pressure, bradykardiya, dystrophic changes of myocardium), bone system (osteopeniya, osteoporosis). 3 months replacement therapy resulted in increasing of IGF-1 and IGF-BP-3 levels and achievement of normal values after 24 months’ treatment. It was no gender differences in the changes of IGF-1 and IGF-BP-3 before puberty. With appearance of signs of puberty we observed slow increasing of IGF-1 and IGF-BP-3 levels. At slowing down growth in patients with signs of puberty scheme of treatment with GH changed: the dose of growth hormone is increased in 1,3-2 times. The long replacement therapy with GH allowd getting satisfactory growth in patients and removing the changes in cardio-vascular, bone systems and lipidogramma.